2004
DOI: 10.1016/j.ijgo.2004.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic evaluation of lower uterine segment thickness in patients of previous cesarean section

Abstract: Ultrasonographic evaluation permits better assessment of the risk of scar complication intrapartum, and could allow for safer management of delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 12 publications
11
71
1
1
Order By: Relevance
“…7 Sen et al conducted a study in North India and reported the rate of successful VBAC to be 63.5%. 8 Various other studies like Vidyadhar et al showing 85% and Shakti V et al showing 72% VBAC in periphery centers. 9,10 A study conducted at LHMC Delhi by Madaan M et al showed a success rate of 53.6%.…”
Section: Discussionmentioning
confidence: 89%
“…7 Sen et al conducted a study in North India and reported the rate of successful VBAC to be 63.5%. 8 Various other studies like Vidyadhar et al showing 85% and Shakti V et al showing 72% VBAC in periphery centers. 9,10 A study conducted at LHMC Delhi by Madaan M et al showed a success rate of 53.6%.…”
Section: Discussionmentioning
confidence: 89%
“…The review comprises 12 studies published between 1988 and 2009 [12,[33][34][35][36][37][38][39][40][41][42][43] including together 1834 women with a previous low transverse caesarean hysterotomy who underwent ultrasound measurement of the thickness of the lower uterine segment at [35][36][37][38][39][40] gestational weeks. In seven of the 12 studies the full lower uterine segment thickness was measured [12,33,36,[38][39][40]42], in four studies the myometrial thickness was measured [34,35,37,43], and in one study both measurements were taken [41].…”
Section: Gestational Weeks Predict Uterine Rupture or Dehiscence?mentioning
confidence: 99%
“…In seven of the 12 studies the full lower uterine segment thickness was measured [12,33,36,[38][39][40]42], in four studies the myometrial thickness was measured [34,35,37,43], and in one study both measurements were taken [41]. Because only three of the 12 studies reported the frequency of uterine rupture separately, the outcome measure was "uterine rupture or uterine dehiscence", i.e.…”
Section: Gestational Weeks Predict Uterine Rupture or Dehiscence?mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Ultrasound evaluation permits better assessment of scar complication intrapartum and could allow for safer management of delivery. 5 The present study was conducted to sonographically evaluate scar thickness in previous cesarean and study the obstetric and perinatal outcome.…”
Section: Introductionmentioning
confidence: 99%